Computed tomography of blunt abdominal trauma - Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Hassan, Radhiana; Che Mohamed, Siti Kamariah; Muhammed Nordin, Ellyda (IIUM Press, International Islamic University Malaysia, 2018)
Radiology is a ‘visual’ field and is best taught and learnt by looking at images rather than reading from text alone. This is the basis when this book was prepared. This book is written to provide a quick and hopefully a useful reference for radiologists, and surgeons and others involved in managing these types of cases including medical officers working in radiology, surgery and emergency departments. It can also be a useful book for medical students, nursing students and allied health students to consolidate their knowledge on this important topic to prepare them for clinical practice in later years. The understanding of imaging findings related to blunt abdominal injuries can facilitate communications among clinicians for optimum patient care.